The Structure of the Narative Texts Written by the Students of ESP - Maya Sari; Stefanus Laga Tukan; Agustinus Ngadiman (Magister Scientiae, 2011)
In line with the objective of Writing 1; making the students capable to write a good recount including a(n) (auto) biography texts and narratives texts in grammatically correct and acceptable sentences in English, the writer, hence, tries to investigate the quality of Writing 1 products, especially the narrative texts they produced. The data sources of the study under report are Writing 1 students’ final semester test papers of the even semester of the academic year of 2006/2007 and 2008/2009 in the EESP of WMSCU. The results of the analyses show that the organization of the narrative of the excellent. Even though the organizational patterns are varied, the readers are still able to follow the compositions with a good understanding and feel the flow of the compositions. In short, those compositions are understandable.